Iron refractory iron deficiency anemia - De Falco, Luigia; Sanchez, Mayka; Silvestri, Laura; Kannengiesser, Caroline; Muckenthaler, Martina; Iolascon, Achille; Gouya, Laurent; Camaschella, Clara; Beaumont, Carole (Haematologica, the hematology journal, 2013)
Iron refractory iron deficiency anemia is a hereditary recessive anemia due to a defect in the TMPRSS6 gene encoding Matriptase-2. This protein is a transmembrane serine protease that plays an essential role in down-regulating hepcidin, the key regulator of iron homeostasis. Hallmarks of this disease are microcytic hypochromic anemia, low transferrin saturation and normal/high serum hepcidin values. The anemia appears in the post-natal period, although in some cases it is only diagnosed in adulthood. The disease is refractory to oral iron treatment but shows a slow response to intravenous iron injections and partial correction of the anemia. To date, 40 different Matriptase-2 mutations have been reported, affecting all the functional domains of the large ectodomain of the protein. In vitro experiments on transfected cells suggest that Matriptase-2 cleaves Hemojuvelin, a major regulator of hepcidin expression and that this function is altered in this genetic form of anemia. In contrast to the low/undetectable hepcidin levels observed in acquired iron deficiency, in patients with Matriptase-2 deficiency, serum hepcidin is inappropriately high for the low iron status and accounts for the absent/delayed response to oral iron treatment. A challenge for the clinicians and pediatricians is the recognition of the disorder among iron deficiency and other microcytic anemias commonly found in pediatric patients. The current treatment of iron refractory iron deficiency anemia is based on parenteral iron administration; in the future, manipulation of the hepcidin pathway with the aim of suppressing it might become an alternative therapeutic approach.
Gesehen am 10.12.2020